FAULT INSPECTION BY AERIAL INFRARED THERMOGRAPHY IN A PV PLANT AFTER A METEOROLOGICAL TSUNAMI - Oliveira, Aline Kirsten Vidal; Aghaei, Mohammadreza; Madukanya, Uzoma Edward; Rüther, Ricardo (Revista Brasileira de Energia Solar, 2019)
Infrared thermography (IRT) has been applied as an effective tool for detecting faults in PV modules. In addition, with the recent development of Unmanned Aerial Vehicles (UAV), they have been used in order to increase the cost-effectiveness and employ IRT for large-scale PV plants or roof-mounted PV systems. With the goal of demonstrating the capabilities of the UAV application, especially in aerial thermography analysis, this article presents an experiment applying UAV based IRT, performed for the fault inspection of a PV plant in South Brazil. The local is a 3 MWp PV plant located in the city of Tubarão in the state of Santa Catharina and consists of three 1 MWp-blocks of different PV technologies. On October of 2016, the plant was affected by a meteorological tsunami, causing several damages. The experiment was focused on the detection of the damages on the polycrystalline PV block of the power plant and a DJI Phantom 3 Advanced was equipped with a lightweight infrared camera to perform the aerial IRT. The measurements in the plant were performed in accordance with the international norm IEC TS 62446-3, under stable radiation and weather conditions, exclusively with irradiances above 800 W/m2 and average wind speeds of 3 m/s. The IRT drone system was essential for identifying damaged and defect portions of the PV power plant fast after the incident. It was possible to detect hot spots, defective bypass-diodes, short- and open-circuited strings. The damages could be noticed even when the UAV flight was at 40 m of altitude. The UAV based IRT assessment helped to identify the defects in a fast manner, without interrupting the power generation. It can be concluded that the technique is very effective, practical and relevant for damage inspection in large PV power plants.